Job Stress and Turnover Intention in Generation Z Teachers: Resilience as a Moderator - Lubis, Rahmi; Syafitri, Nellinda; Alyani, Nurin Nadhira; Maylinda, Risky Nurlita; Anda, Riski; Zulfiyanti, Novi (Universitas Islam Indonesia, 2024)
Teaching is a demanding profession that can jeopardize the physical and mental health of teachers. Generation Z teachers, born between 1995 and 2009, are innovative, flexible, and adaptive in the teaching approach but dislike complicated rules and tend to change job, resulting to increased turnover intention. One of the predictors affecting turnover intention is job stress, an aspect that has not been previously explored. Therefore, this correlational quantitative study aimed to investigate the role of resilience in determining the magnitude of the effect of job stress on turnover intention. The participants were 170 Generation Z teachers from private elementary schools in District X Medan. The study instrument included job stress scale adapted from Dinyati (2019), turnover intention scale from Bothma & Roodt (2013), and resilience scale from Connor and Davidson (2003). The SEM test results showed that resilience played a crucial role in determining the strength of the effect of job stress. The effect of stress on turnover intention decreased with increase in resilience and vice versa.